Doenças de caprinos no Centro-Oeste do Brasil - Rosa, Fábio Brum (2017)
The data herein described is a compilation of retrospective and prospective studies of diseases in goats diagnosed at the Laboratório de Anatomia Patologica at the Universidade Federal de Mato Grosso do Sul. This investigation examined 74 necropsy reports of goats obtained for the period between January 2012 and August 2015. The results yielded 72 conclusive diagnoses (in 6 cases there was more than one diagnosis by necropsy), and 16 it was not possible to conclude for a diagnosis.. Of the 72 conclusive diagnoses, 65.3% were infectious and parasitic diseases, 25.0% were intoxications and toxinfections, and 8.3% were metabolic and nutritional diseases. Other disorders were diagnosed on one occasion only (1.4%). Haemonchosis was the most prevalent condition in all diagnoses (27.8%), followed by bilateral bronchopneumonia (20.8%) and poisoning by Brachiaria decumbens (18.1%). Four scientific papers resulted from this study: (1) Spontaneous poisoning by Brachiaria decumbens in goats; (2) Renal encephalopathy due to acute renal failure in a goat; (3) Granulomatous leptomeningitis in a goat associated with infection by Cryptococcus neoformans and (4) Hepatogenous chronic copper toxicosis associated with grazing Brachiaria decumbens in a goat. These four papers are already published and attached to this thesis.